Observational study of the medical management of patients with peripheral artery disease. Issue 9 (1st July 2019) - Saratzis, A.; Jaspers, N. E. M.; Gwilym, B.; Thomas, O.; Tsui, A.; Lefroy, R.; Parks, M.; Htun, V.; Mera, Z.; Thatcher, A.; Bosanquet, D.; Forsythe, R.; et al.
Abstract : Background: Previous research has suggested that patients with peripheral artery disease (PAD) are not offered adequate risk factor modification, despite their high cardiovascular risk. The aim of this study was to assess the cardiovascular profiles of patients with PAD and quantify the survival benefits of target‐based risk factor modification. Methods: The Vascular and Endovascular Research Network (VERN) prospectively collected cardiovascular profiles of patients with PAD from ten UK vascular centres (April to June 2018) to assess practice against UK and European goal‐directed best medical therapy guidelines. Risk and benefits of risk factor control were estimated using the SMART‐REACH model, a validated cardiovascular prediction tool for patients with PAD. Results: Some 440 patients (mean(s.d.) age 70(11) years, 24·8 per cent women) were included in the study. Mean(s.d.) cholesterol (4·3(1·2) mmol/l) and LDL‐cholesterol (2·7(1·1) mmol/l) levels were above recommended targets; 319 patients (72·5 per cent) were hypertensive and 343 (78·0 per cent) were active smokers. Only 11·1 per cent of patients were prescribed high‐dose statin therapy and 39·1 per cent an antithrombotic agent. The median calculated risk of a major cardiovascular event over 10 years was 53 (i.q.r. 44–62) per cent. Controlling all modifiable cardiovascular risk factors based on UK and European guidance targets (LDL‐cholesterol less than 2 mmol/l, systolic BP under 140 mmHg, smoking cessation, antiplatelet therapy) would lead to an absolute risk reduction of the median 10‐year cardiovascular risk by 29 (20–38) per cent with 6·3 (4·0–9·3) cardiovascular disease‐free years gained. Conclusion: The medical management of patients with PAD in this secondary care cohort was suboptimal. Controlling modifiable risk factors to guideline‐based targets would confer significant patient benefit. Abstract : Previous research has suggested that the medical management of patients with peripheral artery disease may be suboptimal. This national project assessed the medical therapy and lipid control of individuals with established peripheral artery disease and compared it against established guidelines/treatment targets. These individuals are currently not receiving appropriate care to address their cardiovascular risk factors, which has an impact on their predicted risk of future major cardiovascular morbidity. New pathways of treatment are required to address this important issue and improve outcomes. CVD, cardiovascular disease; ARR, absolute risk reduction. Room for improvement